2015
DOI: 10.1186/s12989-016-0113-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-allergen interactions mediate human allergic responses: protein corona characterization and cellular responses

Abstract: BackgroundEngineered nanomaterials (ENMs) interact with different biomolecules as soon as they are in contact, resulting in the formation of a biomolecule ‘corona’. Hence, the ‘corona’ defines the biological identity of the ENMs and could affect the response of the immune system to ENM exposure. With up to 40 % of the world population suffering from type I allergy, a possible modulation of allergen effects by binding to ENMs is highly relevant with respect to work place and consumer safety. Therefore, the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 79 publications
1
45
0
Order By: Relevance
“…Therefore, studies on the interaction of nanomaterials with cells and biomolecules can open new avenues in understanding the structural characteristic required for the bio-affinity of NPs toward pharmacological activity. [1][2][3][4] Nanomaterials can demonstrate a strong influence on cell viability and structural and corresponding functional features of biomolecules. Therefore, continuous interest has been focused toward comprehending the fundamental effects of NPs for interaction with biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies on the interaction of nanomaterials with cells and biomolecules can open new avenues in understanding the structural characteristic required for the bio-affinity of NPs toward pharmacological activity. [1][2][3][4] Nanomaterials can demonstrate a strong influence on cell viability and structural and corresponding functional features of biomolecules. Therefore, continuous interest has been focused toward comprehending the fundamental effects of NPs for interaction with biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there has been no report on the allergy‐enhancing effect of silver NPs. Very recently, it was reported that when Der p 1, an allergen closely related to that used in our study, was bound to nanogold, IgE‐dependent basophil degranulation and the proteolytic activity were increased …”
Section: Resultsmentioning
confidence: 54%
“…The formation of unique protein coronas based on the capping material has been reported to influence the inflammatory response to AgNP by modulating the way nanomaterials interact with cells or tissues [5658]. One study of gold nanoparticles revealed different capping agents have the ability to elicit differential effects on both in vitro and in vivo toxicity [59].…”
Section: Discussionmentioning
confidence: 99%